The pursuit of enlightenment and the Singaporean buddhist monastics. - Nguyen, Thi Gia Hoang. (2011)
The primary goal of this paper is to understand why some Singaporeans decide to follow the Buddhist monastic way of life. Situating the research in the context of the modern, capitalist, multicultural Singapore society, I have used Berger and Luckmann’s (1966) sociology of knowledge to explore and explain the process of becoming Buddhist monastics of some Singaporeans. Through field work at various Buddhist sites in Singapore and in-depth interviews with Singaporean Buddhist monastics who are residing locally and overseas, the findings reveal that the process of becoming a Buddhist monastic involves the socialization of individuals into the Buddhist reality, the de-reification of other realities, and lastly, the re-socialization into the Buddhist monastic reality. These findings are later linked to broader changes and persistence in Buddhism in Singapore, which have been characterized by some authors as a trend towards Reformist Buddhism.